Germany : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper analyzes the macroeconomic impact of targeted labor market reforms aimed at boosting employment and labor productivity and the price responsiveness of German residential investment. Germany's population is getting older, and potential growth is set to decline. Demographic projections suggest that labor force will start declining around 2020, and will drop at an accelerating pace once immigration flows normalize. After years of stagnation, German housing prices and new residential rents have increased more steeply since 2009, especially in large cities. This paper provides econometric evidence that supply response to changes in housing prices has declined over the past several years and discusses how various housing policies can foster this response.